2023
DOI: 10.3390/w15162983
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Cooling Effect of Blue-Green Spaces: Implications for Urban Heat Island Mitigation

Pritipadmaja,
Rahul Dev Garg,
Ashok K. Sharma

Abstract: The Urban Heat Island (UHI) effect is a significant concern in today’s rapidly urbanising cities, with exacerbating heatwaves’ impact, urban livelihood, and environmental well-being. This study aims to assess the cooling effect of blue-green spaces in Bhubaneswar, India, and explore their implications for mitigating UHI effects. Satellite images were processed with Google Earth Engine (GEE) to produce information on the blue-green spaces’ land surface temperatures (LST). The Normalised Difference Vegetation In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 66 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…In order to explore the elements relevant to mitigating heat disasters, researchers in various fields have studied various urban cooling measures, including the use of cooling materials and colors [19,20], as well as the planning of urban blue-green spaces (UBGSs) [21]. Numerous studies have demonstrated that UBGSs may greatly reduce urban heat, lower surface temperatures, and be more cost-effective [22,23]. Green spaces (including forests, urban parks, green roofs, and other vegetated areas) can cool the air through evaporation and also reduce the ground temperature by reducing the solar radiation directly reaching the ground through shade [24].…”
Section: Introductionmentioning
confidence: 99%
“…In order to explore the elements relevant to mitigating heat disasters, researchers in various fields have studied various urban cooling measures, including the use of cooling materials and colors [19,20], as well as the planning of urban blue-green spaces (UBGSs) [21]. Numerous studies have demonstrated that UBGSs may greatly reduce urban heat, lower surface temperatures, and be more cost-effective [22,23]. Green spaces (including forests, urban parks, green roofs, and other vegetated areas) can cool the air through evaporation and also reduce the ground temperature by reducing the solar radiation directly reaching the ground through shade [24].…”
Section: Introductionmentioning
confidence: 99%